2015
DOI: 10.18632/oncotarget.3527
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 and HER-3 expression in liver metastases of patients with colorectal cancer

Abstract: ObjectiveIn this study, we evaluate the frequency of HER-2 and HER-3 expression in liver metastases from patients with colorectal cancer (CRLM). We analyzed the potential of HER-2 and HER-3 as therapeutic targets and evaluated their prognostic value.Patients and MethodsOverall 208 patients with CRLM were enrolled. HER-2 and HER-3 expression were determined in metastatic tissue of diagnostic punch biopsies (n = 29) or resection specimens (n = 179). The results of immunohistochemistry (IHC) scoring and In-situ-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
3
22
1
Order By: Relevance
“…Although ERBB2 has been described to have oncogenic properties, we demonstrated that expression was significantly down-regulated in UC patients who harbored neoplastic lesions. This is consistent with findings from previous studies which concluded that a low percentage of sporadic colon cancers are HER2 positive as well as a recently published analysis that identified a low rate of ERBB2-activating mutations in IBD-associated neoplasia (4143). …”
Section: Discussionsupporting
confidence: 93%
“…Although ERBB2 has been described to have oncogenic properties, we demonstrated that expression was significantly down-regulated in UC patients who harbored neoplastic lesions. This is consistent with findings from previous studies which concluded that a low percentage of sporadic colon cancers are HER2 positive as well as a recently published analysis that identified a low rate of ERBB2-activating mutations in IBD-associated neoplasia (4143). …”
Section: Discussionsupporting
confidence: 93%
“…However, the role and regulatory mechanisms of HER3 in CRC cells remain unclear. Preclinical studies reported that HER3 is expressed in more than 75% of CRC primary and metastatic tumors (34,35), and its overexpression mediates CRC cell resistance to anti-EGFR therapy (3638).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 32 articles were screened for titles and abstracts, of which 24 were excluded (19 articles with insufficient data and 5 with methods other than IHC to evaluate the Her3 status). Finally, 8 studies [ 14 17 , 19 22 ] were included in this meta-analysis. In these studies, the proportion of Her3 overexpression ranged from 13.4% to 80.3%, and the proportion of high Her3 expression in all patients was 65.9% (1131/1716).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the cut-off for Her3 overexpression and clinicopathological factors. Her3 expression in 6 studies [ 15 17 , 19 20 , 22 ] was graded as follows: grade 0 to 1 was categorized as low expression and grade 2 to 3 as high expression. Furthermore, 2 studies [ 14 , 21 ] were evaluated according to the Rajkumar score, and the specificity for estimating Her-3 expression was set at ≤8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation